2016
DOI: 10.4172/2161-0444.1000415
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Molecular Modelling and Biological Evaluation of Novel α-Naphtholhydroxamate Derivatives as Potential Anticancer Agents

Abstract: Chemotherapy is one of the treatment options for cancer. A major problem in cancer chemotherapy is the lack of selective toxicity of many commonly used anti-cancer agents towards tumor tissue compared to normal tissue. Studies have shown that α-naphthol is selectively toxic to cultures of human tumor tissue compared to normal tissues in vitro. Hence, this study was conducted to synthesize a series of new hydroxamate derivatives containing α-naphthol nucleus by the reaction of naphthol acetic acid with amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…More so, it is also reported to suppress CSCs in human breast carcinoma cell line MDA‐MB‐231 (Takehara, Hoshino, Namba, Yamakawa, & Mizushima, 2011). In both Series C and D , we incorporated α‐ and β‐naphthol core structures, respectively, based on our earlier findings (Sahu et al, 2019) and the reported literature of naphthol derivatives as anticancer agents (Abdelrahim, Mohan, Albarrati, Makeen, & Safhi, 2016; Das, Reddy, Kashanna, Mamidyala, & Kumar, 2012; Osowole, Kempe, Schobert, & Effenberger, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More so, it is also reported to suppress CSCs in human breast carcinoma cell line MDA‐MB‐231 (Takehara, Hoshino, Namba, Yamakawa, & Mizushima, 2011). In both Series C and D , we incorporated α‐ and β‐naphthol core structures, respectively, based on our earlier findings (Sahu et al, 2019) and the reported literature of naphthol derivatives as anticancer agents (Abdelrahim, Mohan, Albarrati, Makeen, & Safhi, 2016; Das, Reddy, Kashanna, Mamidyala, & Kumar, 2012; Osowole, Kempe, Schobert, & Effenberger, 2011).…”
Section: Introductionmentioning
confidence: 99%